2018
DOI: 10.1080/17425255.2018.1476488
|View full text |Cite
|
Sign up to set email alerts
|

A current structural perspective on PXR and CAR in drug metabolism

Abstract: Pregnane X receptor (PXR) and the constitutive androstane receptor (CAR) are two members of the nuclear receptor superfamily that play major roles in the expression of various drug metabolism enzymes and are known for their ligand promiscuity. As with other nuclear receptors, PXR and CAR are each composed of a ligand-binding domain (LBD) and a DNA-binding domain (DBD) connected by a hinge region. Areas covered: This review focuses on the information obtained over the last 15+ years from X-ray crystallography s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 72 publications
0
35
0
1
Order By: Relevance
“…Moreover, ARQ-197 also inhibited the activation of PXR, which is the key regulator for exogenous drug metabolism and detoxification in cells. 79,80 Previous studies have also shown that sorafenib can act as a ligand/agonist for PXR during treatment, promoting the expression of PXR downstream drug resistance-related genes by inducing PXR's transcription factor activity, ultimately resulting in sorafenib resistance. 47,81 In HCC cells, the transcription factor ETS-1, an important effector of HGF/c-MET signaling pathway, could function as a co-regulator of PXR and enhance sorafenib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ARQ-197 also inhibited the activation of PXR, which is the key regulator for exogenous drug metabolism and detoxification in cells. 79,80 Previous studies have also shown that sorafenib can act as a ligand/agonist for PXR during treatment, promoting the expression of PXR downstream drug resistance-related genes by inducing PXR's transcription factor activity, ultimately resulting in sorafenib resistance. 47,81 In HCC cells, the transcription factor ETS-1, an important effector of HGF/c-MET signaling pathway, could function as a co-regulator of PXR and enhance sorafenib resistance.…”
Section: Discussionmentioning
confidence: 99%
“…The LBD is characterized by the presence of a hydrophobic pocket that entraps ligands. Unlike the ligand cavity of most NRs, the binding pocket of PXR is prominent for being large and highly flexible, which enables it to accommodate ligands of great diversity in terms of their chemical scaffold, size, lipophilicity, and surface area . Figure shows reported modulators of PXR in a manner that illustrates the large chemical space that they encompass, thus providing an impression of the extensive range of their physiochemical properties.…”
Section: Current Status Of Pxr Antagonist Development Challenges Anmentioning
confidence: 99%
“…PXR is crucial in regulating the expression of CYP3A4 enzyme, which mediates the metabolic process of many clinical prescription drugs (Liu, Lim, & Hu, ). Similar to the other nuclear receptors, PXR also includes DNA‐binding domain and ligand‐binding domain (Buchman, Chai, & Chen, ). PXR can be activated by combining with a large number of ligands for various structural and chemical properties (Banerjee, Robbins, & Chen, ), including steroids (Chianese, Sepe, & Limongelli, ), rifampicin (Kodama, Yamazaki, & Negishi, ), bile acid (Wang, Wang, & Lu, ), dexamethasone (Ponce‐Ruiz, Rojas‐García, & Barrón‐Vivanco, ), phenobarbital (Chen, Bao, & Piekos, ), HIV protease inhibitor ritonavir (Liu, Xu, & Hui, ), hyperforin (Taneja, Chu, & Maturu, ), and so forth.…”
Section: Introductionmentioning
confidence: 99%